Evaluasi Tampilan Antarmuka QGIS Dan ArcGIS Menggunakan Pendekatan User-Centered Design (UCD) : Studi Kasus Fungsi Geoprocessing Tools - Fathin Naufal Hawi; Fatwa Ramdani; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Interface quality is a great influence on usefulness of Geographic Information System (GIS) but it not yet to be important points in GIS and issues of GIS application difficult to understand by users because design of user interface than technical problems. This research is aimed at doing a comparison to applications QGIS and ArcGIS using user-centered design method. The usability testing shows from the aspect of effectiveness in every function tested are likely to be more high effectiveness on the application of QGIS in terms of the function 73% of the intersect, 73% buffer, 53% dissolve, 53% merge and 60% union while ArcGIS just high on 33% clip. On the aspect of efficiency with goals/min units, there's no function can be completed in one minutes, every task requires measures varied to achieve its goals, but the results show highest levels of efficiency on ArcGIS in terms of clip in 0,31, intersect in 0,38, dissolve in 0,90. While QGIS is higher on buffer in 0,88, merge in, and union in 0,80. The aspect of satisfaction show ArcGIS are likely to be more high satisfaction scores with 68,5 compared to QGIS with 54,5.